Problematika Sakralitas dalam Media Hiburan: Telaah Fikih terhadap Game “Ghaib”: The Problematics of Sacredness in Entertainment Media: A Fiqh Analysis of the Game “Ghaib” - Salman Al Farisi (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
The presence of holy Islamic material in popular media is a grave matter morally and legally—particularly when Qur'anic passages are used in entertainment media.